Disentangling chronic regeneration failure in endangered woodland ecosystems. Issue 1 (10th January 2020) - Bennett, Ami; Duncan, David H.; Rumpff, Libby; Vesk, Peter A.
Abstract: Ecological restoration of degraded ecosystems requires the facilitation of natural regeneration by plants, often augmented by large‐scale active revegetation. The success of such projects is highly variable. Risk factors may be readily identifiable in a general sense, but it is rarely clear how they play out individually, or in combination. We addressed this problem with a field experiment on the survival of, and browsing damage to, 1275 hand‐planted buloke ( Allocasuarina luehmannii ) seedlings in a nationally endangered, semi‐arid woodland community. Buloke seedlings were planted in 17 sites representing four landscape contexts and with three levels of protection from kangaroo and lagomorph browsing. We censused seedlings and measured herbivore activity four times during the first 400 d post‐planting and fitted models of mortality and browse hazard to these data using survival analysis. Increasing lagomorph activity was associated with higher mortality risk, while kangaroo activity was not. Seedling survival was lowest for each treatment within extant buloke woodland, and the highest survival rates for guarded seedlings were in locations favored by lagomorphs. Damage from browsing was nearly ubiquitous after one year for surviving unguarded seedlings, despite moderate browser activity. On average, unguarded seedlings showed a decline in height, whereas fully guarded seedlings grew 2.3 cm across the survey period. This study demonstrates buloke seedlings should be protected from browsers, even with browsers maintained at moderate to low density, and the location that maximizes survival, and possibly growth rates, is adjacent to dunes. Further work will test this heuristic in an analysis of cost‐effective revegetation strategies for this endangered community.